Students problems in the introduction section of thesis writing - Helmanda, Cut Mawar; Novrizal, Ade M. Novan; Safura, Siti (Accentia: Journal of English Language and Education, 2022)
This study aims to investigate undergraduate students problems in writing the Introduction section of their thesis. The study used the qualitative research method, employing interview to collect the necessary data. The study took ten students of English Education Department at Universitas Muhammadiyah Aceh, Aceh Province, as the sample. The technique used to analyze the data was descriptive analysis. The results of the study showed that most problems that students faced in writing thesis in the Introduction section consisted of lack of the supporting theories, lack of paraphrasing skills, lack of motivation, lack of grammatical knowledge, and lack of writing organization skills. One of the causes of their problems was low English competence. The students, however, tried to solve their problems by having routine consultation with thesis supervisors and reading many sources related with their thesis topics.